Asymmetric alliances and information systems : issues and prospects - Said, Karim; Korbi, Fadia Bahri (Hoboken : Wiley, 2017)
This book explores the impact of information systems on the management of North-South asymmetric strategic alliances through a series of in-depth case studies which analyze different types of partnerships. Positioned at the heart of the value creation process, the choice of information system seems to be becoming a strategic issue which should be centered not only on the organizational decisions related to the type of alliance but also the management systems of each of the partners. The authors provide an understanding of the nature of this relationship between the organizational structure and the method of information system integration in asymmetric alliances. The in-depth analysis of strategic alliance case-studies illustrates the different methods of information system integration, which are themselves linked to the organisational and structural choices of the alliance. These methods are characterized by information-sharing and coordination mechanisms as well as the balance of control over shared activities developed by the distinct partners.
5.1.4. Perimeter of activity of the alliance -- 5.1.5. Governance model of the alliance -- 5.2. Role of IS in managing alliance DELTA -- 6. Case KAPPA -- 6.1. Characteristics of alliance KAPPA -- 6.1.1. Organizational form of the alliance -- 6.1.2. Ends sought by both partners -- 6.1.3. Resources committed by the partners -- 6.1.4. Perimeter of activity of alliance KAPPA -- 6.1.5. Governance model of the alliance -- 6.2. The role of IS in managing alliance KAPPA -- 7. Case IOTA -- 7.1. Characteristics of alliance IOTA -- 7.1.1. Organizational form of the alliance -- 7.1.2. Ends sought by each party -- 7.1.3. Resources committed by the partners -- 7.1.4. Perimeter of activity of the alliance -- 7.1.5. Governance model of the alliance -- 7.2. Role of IS within alliance IOTA -- Conclusion: The Role of IS in Managing Asymmetric Alliances -- Bibliography -- Index -- Other titles from iSTE in Information Systems, Web and Pervasive Computing -- EULA.
Includes bibliographical references and index.
Print version record.
Keywords: Strategic alliances (Business); Business networks; COMPUTERS -- Information Technology; Business networks; Strategic alliances (Business); Electronic books